Early Marriage Incidence Before and During the Covid-19 Pandemic: A Case Study in Palangka Raya City - Annah, Itma; Hadina, Meirinda; Damiti, Sukmawati A. (SIGn Journal of Public Health, 2024)
The COVID-19 pandemic has triggered a significant global surge in early marriage cases; however, specific local-level dynamics with unique urban demographic characteristics, such as in Palangka Raya City, are rarely investigated in depth. This quantitative descriptive study with a comparative design aimed to analyze the differences in the incidence and demographic characteristics of individuals entering early marriage in Palangka Raya City before (2019) and during (2020) the pandemic, utilizing secondary data from 172 marriage dispensation applications at the Religious Court. The results demonstrated a drastic increase in cases by more than threefold, from 40 cases in 2019 to 132 cases in 2020. This surge was dominated by the late adolescence age group (15 – 19 years), which accounted for 73.48% of the total cases in 2020. The most prominent finding was a shift in the educational profile, where the involvement of senior high school-educated adolescents increased sharply to 46.21% during the pandemic, indicating that educational disruption and online schooling fatigue served as driving factors equally as strong as economic pressure. Furthermore, the Dayak ethnic group experienced a significant proportional increase in involvement, affirming the role of local cultural factors in responding to the crisis. This study concludes that the COVID-19 pandemic exacerbated adolescent vulnerability to early marriage through the mechanisms of learning loss and economic instability, which carries serious implications for increased risks of reproductive health issues and future stunting. Consequently, this demands multisectoral interventions that integrate educational and economic strengthening with cultural approaches.